Revitalizing Political Agency: Contextual Politics against Discrimination - Venditti, Valeria (Phenomenology and Mind, 2019)
This article centres on the predicament of political discrimination insofar as inclusive policies fail to address it and end up impoverishing political agency. On the one hand, inclusion plays out as a powerful political tool, as people are believed to gain access to forms of recognition granting legal protection and social visibility. On the other hand, however, my claim is that most models of political inclusion require people’s adhering to fixed policy matrixes that do not allow the articulation of forms of life falling short of the standards that these matrixes incorporate. The following analysis will be devoted to foregrounding the limits of inclusion and to advancing an alternative model that revitalizes political agency by valuing practices carried out in smaller social networks of solidarity – ones that entail some sort of normativity but are characterised by fluidity and proximity. On this alternative account, inclusion comes to be reframed as a web of relations and relocated within the subject’s reach. Whether in a vertical or a horizontal exchange, the subject becomes part of a collective that is not configured as the mainstream or the majority, nor does it saturate the subject’s life. Rather, inclusive processes appear as sectional moments of renegotiation and rearticulation of one’s subjectivity exposed to the constant flux of daily interactions.